Editorial [Hot Topic: Macrocyclic Lactones in Antiparasitic Therapy (Guest Editor: Aranzazu Gonzalez-Canga)] - Gonzalez-Canga, Aranzazu (Current Pharmaceutical Biotechnology, 2012)
Full text available.